MENYINGKAP TUHAN MELALUI PENGETAHUAN HINDU DALAM TEKS BHUWANA SANGKSEPA (KAJIAN TEO-FILOSOFI) - Prasanthy Devi Maheswari (Sanjiwani: Jurnal Filsafat, 2020)
God is the object of science, in Hindu knowledge says that God is the main and first source of knowledge. Studying the scriptures is the main way in revealing knowledge about God. The purpose of this research is to find knowledge about God in the text Bhuwana Sangkṣepa. The benefit is to open up the insights and courage of academics in interpreting sacred texts. This research is a library research with qualitative methods. The approach used between a combination of two frameworks is called the theo-philosophy. This text provides knowledge about God who is the Source of All, Transcendent God (God Beyond/Far from Human Understanding), God in Nirguna Brahma Terminology (Formless/Unmanifest), Transcendent-Immanent God (God is closer to understanding Humans), Nir-Saguna Brahman Terminology of God with Symbols (Nyasa), Immanent God (in consciousness or in the human mind). And then God in the Saguna Brahma Terminology (Manifested God) which includes the form of Gods (Sarva-Nama Rupa), God sink in the universe (macrocosm) and God resides in the Human Self (microcosm).